Characteristics and accumulation of heavy metals in sediments originated from an electroplating plant - Hang, Xiaoshuai; Wang, Huoyan; Zhou, Jianmin; Du, Changwen; Chen, Xiaoqin (Journal of hazardous materials, 2009)
Heavy metals in river water and sediments originated from an electroplating plant in Jiangsu Province of China were studied and analyzed for their environmental impact. The results indicated that the wastewater from the plant degraded the quality of the aquatic environment downstream from the plant. In surface water, considerable concentrations of Cu, Ni, Zn, Mn and Cr were present at the sites near the plant. Unsafe levels of Cu were observed at all sites, and unsafe levels of Ni, Zn, and Cr were present at some sites. Significant accumulation of Ni, Cu, Zn and Cr was identified, and heavy metal longitudinal distribution in sediments was similar to that in water. The contents of Ni, Cu and Cr at all sites and Zn at some sites were likely to result in harmful effects on the environment. The risks posed by Ni, Cu, Zn and Cr in water and sediments decreased with increasing downstream distance. Moreover, a modified sequential extraction procedure was employed to determine exchangeable, carbonate-bound, iron–manganese oxide bound, organic matter bound and residual fractions of metals in sediments. The results showed that Ni was distributed in every fraction except for iron–manganese oxide bound, significant Mn exhibited in exchangeable fractions, and high percentage of Cu was in the organic matter and residual fractions. Residual fraction was the dominant fractions for Pb and Zn. According to RACs, Ni and Mn posed a high risk to the environment, Zn exhibited medium to high risk, Cu had low to high risk, and Pb possessed a low to medium risk.